Dynamic Regulation of the Molecular Mechanisms of Regulatory T Cell Migration in Inflamed Skin - Norman, M. Ursula; Chow, Zachary; Snelgrove, Sarah L.; Prakongtham, Peemapat; Hickey, Michael J. (Frontiers in Immunology, 2021)
The presence of regulatory T cells (Tregs) in skin is important in controlling inflammatory responses in this peripheral tissue. Uninflamed skin contains a population of relatively immotile Tregs often located in clusters around hair follicles. Inflammation induces a significant increase both in the abundance of Tregs within the dermis, and in the proportion of Tregs that are highly migratory. The molecular mechanisms underpinning Treg migration in the dermis are unclear. In this study we used multiphoton intravital microscopy to examine the role of RGD-binding integrins and signalling through phosphoinositide 3-kinase P110delta (PI3K p110delta) In intradermal Treg migration in resting and inflamed skin. We found that inflammation- induced Treg migration was dependent on RGD-binding integrins in a context-dependent manner. Alpha v integrin was important for Treg migration 24 hours after induction of inflammation, but contributed to Treg retention at 48 hours, while beta1 integrin played a role in Treg retention at the later time point but not during the peak of inflammation. In contrast, inhibition of signalling through PI3K p110delta reduced Treg migration throughout the entire inflammatory response, and also in the absence of inflammation. Together these observations demonstrate that the molecular mechanisms controlling intradermal Treg migration vary markedly according to the phase of inflammatory response.